2016
DOI: 10.3389/fpsyg.2016.01166
|View full text |Cite
|
Sign up to set email alerts
|

On the Intentionality of Cultural Products: Representations of Black History As Psychological Affordances

Abstract: A cultural-psychological analysis emphasizes the intentionality of everyday worlds: the idea that material products not only bear psychological traces of culturally constituted beliefs and desires, but also subsequently afford and promote culturally consistent understandings and actions. We applied this conceptual framework of mutual constitution in a research project using quantitative and qualitative approaches to understand the dynamic resonance between sociocultural variance in Black History Month (BHM) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 66 publications
(77 reference statements)
4
90
0
Order By: Relevance
“…For instance, previous studies (Salter & Adams, 2016) have shown that mainstream commemorations of Black History Month in majority-White schools in the U.S.A. tend to focus on issues of diversity and typically fail to mention details about the racist national past. These cultural practices afford both ignorance about the defining role of racism in U.S. society and opposition to policies that might address this injustice.…”
Section: Memory Influences Identitymentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, previous studies (Salter & Adams, 2016) have shown that mainstream commemorations of Black History Month in majority-White schools in the U.S.A. tend to focus on issues of diversity and typically fail to mention details about the racist national past. These cultural practices afford both ignorance about the defining role of racism in U.S. society and opposition to policies that might address this injustice.…”
Section: Memory Influences Identitymentioning
confidence: 99%
“…In contrast, commemorations of Black History Month in majority-Black schools tend to showcase more critical accounts of Black history that draw attention to historical injustices and inequalities. Exposure to these constructions of history afford greater perception of racism in American society and stronger endorsement of anti-racism policies than exposure to mainstream constructions that emphasize celebratory achievements of particular individuals (Salter & Adams, 2016).…”
Section: Memory Influences Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the topic of memory, this approach emphasizes that understandings of the past are not the sole property of atomized individual minds, but develop through engagement with commemoration practices, cultural products, and other cultural tools for memory. These tools include relatively explicit forms such as university entrance exams (Kurtiş, Soylu Yalcinkaya, & Adams, 2017, this section), museum exhibits (Mukherjee, Salter, & Molina, 2015), monuments (Licata & Klein, 2010), and classroom displays (Salter & Adams, 2016). They also include relatively implicit forms such as the ecological association between "the Iraqi regime" and the "attacks of September the 11th" that Bush Related to this emphasis on material manifestations of mind is an appreciation for the intentionality of everyday worlds (Salter & Adams, 2016;see Shweder, 1990).…”
Section: Collective Memory: a Cultural-psychological Approachmentioning
confidence: 99%